Propofol Pretreatment Inhibits Liver Damage in Mice with Hepatic Ischemia/Reperfusion Injury and Protects Human Hepatocyte in Hypoxia/Reoxygenation - Li, Jing; Wang, Ruiqi; Chen, He; Yang, Yu; Yang, Xinyuan; Wang, Wei (Turkish Journal of Gastroenterology, 2023)
Background/Aims: The major complication of liver resection is hepatic ischemia/reperfusion injury. Propofol appears to have organprotective effects. Our study aimed to study the protective role of propofol against hepatic ischemia/reperfusion injury and the potential mechanisms. Materials and Methods: Mice and human hepatocytes (LO2) were used to establish 2 models: the ischemia/reperfusion injury model in vivo and the hypoxia/reoxygenation model in vitro, respectively. Alanine and aspartate aminotransferase serum levels were detected to evaluate the extent of hepatic cellular injury. Malondialdehyde, superoxide dismutase, glutathione, and catalase expression levels were measured to evaluate the oxidative damage in mice liver. Lactate dehydrogenase levels were detected for hepatocyte cytotoxicity severity. Nuclear factor, erythroid-like 2 and heme oxygenase 1 expression levels were detected. Results: In the ischemia/reperfusion model, propofol pretreatment significantly reduced the alanine aminotransferase and aspartate aminotransferase expression levels, alleviating the hepatic cellular injury. Propofol also protected the mice liver from oxidative damage. In the hypoxia/reoxygenation model, propofol pretreatment reduced lactate dehydrogenase expression levels, suggesting its protective effects in LO2 cells. Furthermore, propofol increased the nuclear factor, erythroid-like 2 and heme oxygenase 1 expression levels both in vivo and in vitro. Conclusion: Propofol acts through the nuclear factor, erythroid-like 2, and heme oxygenase 1 pathway to protect the mice liver against ischemia/reperfusion injury and hepatocytes against hypoxia/reoxygenation injury. Propofol should be used as an effective therapeutic drug for hepatic ischemia/reperfusion injury.